(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: CSOM is associated with functional damage to the ear which can present as SNHL; however published literature shows mixed associations. Study design and setting: Cross-sectional observational study at Jinnah Postgraduate Medical Center, Karachi, Pakistan. Methodology: The study sampling technique was non-probability consecutive sampling technique. Patients of either gender and between the ages of 10-50 years, diagnosed with CSOM within the last six months were included while patients with a previous history of SNHL, usage of ototoxic drugs, trauma to ear or those not willing to give consent for the study were excluded. SPSS v23.0 was used for data analysis and chi-square test was applied, keeping p-value of <0.05 as statistically significant. Results: From the total of 200 patients with mean age of patients 24.7 ± 8.42 years. The mean duration of CSOM was 6.56 ± 4.28 years. 145 (72.5 %) were male while 55 (27.5 %) female. SNHL was found to be positive in 36 (18 %) of patients while 165 (82 %) were negative for SNHL. With respect to duration to disease, SNHL was reported to be positive in 11 (10.9 %) of patients having duration of CSOM between 2-6 years while in 25 (25.3 %) of patients having CSOM for over 6 years. A significant difference of p-0.008 was observed in both the groups. Conclusion: According to the results of this study, SNHL is significantly associated with CSOM with higher frequencies observed in males and in patients with CSOM for longer durations.